Differences in the attitudes towards resuscitation of extremely premature infants between neonatologists and obstetricians: a survey study in China - Wang, Dan; Li, Li; Ming, Bo-Wen; Ou, Chun-Quan; Han, Tao; Cao, Jingke; Xie, Wenyu; Liu, Changgen; Feng, Zhichun; Li, Qiuping (Frontiers in Pediatrics, 2023)
Objectives: Neonatologists and obstetricians are crucial decision-makers regarding the resuscitation of extremely preterm infants (EPIs). However, there is a scarcity of research regarding the differing perspectives on EPI resuscitation between these medical professionals.We aim to determine the differences and influential factors of their attitudes towards EPIs resuscitation in China.: This cross-sectional study was conducted in public hospitals of 31 provinces in Chinese mainland from June to July 2021. Influential factors of binary variables and those of ordinal variables were analyzed by modified Poisson regression models and multinomial logistic regression models due to the invalid parallel line assumption of ordinal logistic regression models, respectively.Results: A total of 832 neonatologists and 1,478 obstetricians who were deputy chief physicians or chief physicians participated. Compared with obstetricians, neonatologists delivered a larger proportion of infants of <28-week gestational age (87.74% vs. 84.91%) and were inclined to think it inappropriate to use 28 weeks as the cutoff of gestational age for providing full care to premature infants (63.34% vs. 31.60%, adjusted prevalence ratio=1.61 [95% CI: 1.46-1.77]), and to suggest smaller cutoffs of gestational age and birth weight for providing EPIs resuscitation. Notably, 46.49% of the neonatologists and 19.01% of the obstetricians believed infants ≤24 weeks' gestation should receive resuscitation.In China, notable disparities exist in attitudes of neonatologists and obstetricians towards resuscitating EPIs. Strengthening collaboration between these two groups and revising the pertinent guidelines as soon as possible would be instrumental in elevating the resuscitation rate of EPIs.